Oral Health Related Quality of Life Among Libyan Adults: A Cross-Sectional Study - El-Refadi, Roba; Greiw, Azza; Herwis, Khadija (Libyan Journal of Dentistry, 2018)
Background: In Libya, assessments of oral health needs were entirely based on traditional clinical measures which failed to identify the perceived impact of oral disorders within population. Objectives: This study intended to study the association of Oral Health Related Quality of Life (OHQoL) and some of the demographic factors and to reveal out the effect of oral health on the life of Libyan adults among Libyan adults accessing private and government health services. Subjects and Methods: A random sample of 778 adults aged 18-65years, from the outpatient department of private and governmental clinics/hospitals in Benghazi, were subjected to structured questionnaire comprising the Arabic version of the UK-Oral Health Related Quality of Life (OHQoL-UK). Results: 63.5% of the participants were females, 36.5% were males. Mean age of the participants were 35 SD±12 years.53.1% of the respondents were from private clinics and hospitals, while 46.9% were from governmental hospitals. There were no significance differences between both clinical setting attainders regarding physical, psychological and social aspects. Conclusion: The present research found that Libyan adults do not perceive many effects and only perceive moderate impact on their lives, as influenced by oral health. The present study also found that the demographic characteristics of gender influenced their perceptions of effects and impact on oral health.